Mutations at the lysosomal acid cholesteryl ester hydrolase gene locus in Wolman disease. - Anderson, R A (1994)
The genomic sequences encoding the human lysosomal acid lipase/cholesteryl esterase (sterol esterase; EC 3.1.1.13) have been isolated and sequenced, and the information has been used to identify mutations in both alleles of the gene from a patient with Wolman disease, an autosomal recessive lysosomal lipid storage disorder. The genomic locus consists of 10 exons spread over 36 kb. The 5' flanking region is G+C-rich and has characteristics of a "housekeeping" gene promoter. One of the identified mutations involves the insertion of a T residue after position 634, resulting in the appearance of an in-frame translation stop signal 13 codons downstream. The second mutation is a T-to-C transition at nucleotide 638. This results in a leucine-to-proline substitution at amino acid 179 and is predicted to lead to the disruption of the alpha-helical structure in a highly conserved region of the protein. These mutations are each capable of completely disrupting the catalytic function of the lysosomal acid cholesteryl ester hydrolase; their presence can account for the extreme phenotype of the lysosomal lipid storage disorder manifested in members of this patient's family.